Studies in the Latin literature and epigraphy in Italian fascism - Lamers, Han; Reitz-Joosse, Bettina; Sanzotto, Valerio (Supplementa humanistica Lovaniensia, 2020)
This book deals with the use of Latin as a literary and epigraphic language under Italian Fascism (1922-1943). The myth of Rome lay at the heart of Italian Fascist ideology, and the ancient language of Rome, too, played an important role in the regime's cultural politics. This collection deepens our understanding of 'Fascist Latinity', presents a range of previously little-known material, and opens up a number of new avenues of research. The chapters explore the pivotal role of Latin in constructing a link between ancient Rome and Fascist Italy; the different social and cultural contexts in which Latin texts functioned in the ventennio fascista; and the way in which 'Fascist Latinity' relied on, and manipulated, the 'myth of Rome' of late nineteenth- and early twentieth-century Italy.